2014
DOI: 10.1902/jop.2014.130686
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and 5‐Year Changes in Periodontal Disease Measures Among Postmenopausal Women: The Buffalo OsteoPerio Study

Abstract: Background Vitamin D is hypothesized to prevent periodontal disease progression through its immune modulating properties and its role in maintaining systemic calcium concentrations. We investigated associations between plasma 25(OH)D (collected 1997–2000) and the five-year change in periodontal disease measures from baseline (1997–2000) to follow-up (2002–2005) among 655 postmenopausal women in a Women’s Health Initiative Observational Study ancillary study. Exploratory analyses were conducted in 628 women who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 29 publications
4
48
1
3
Order By: Relevance
“…Together, the study results correlate with other recent findings within the Buffalo OsteoPerio Study in which an inverse association between 25(OH)D and gingival bleeding, an acute measure of periodontal inflammation, has been observed, 6 and no association between 25(OH)D and alveolar crestal height, a chronic measure of oral bone loss, or changes in alveolar crestal height over time has been reported 6 , 34 . The finding of the present study in the OsteoPerio Study suggest that vitamin D may be more influential during the earlier, acute phase of periodontal disease than in prevention of chronic periodontal disease and subsequent tooth loss.…”
Section: Discussionsupporting
confidence: 90%
“…Together, the study results correlate with other recent findings within the Buffalo OsteoPerio Study in which an inverse association between 25(OH)D and gingival bleeding, an acute measure of periodontal inflammation, has been observed, 6 and no association between 25(OH)D and alveolar crestal height, a chronic measure of oral bone loss, or changes in alveolar crestal height over time has been reported 6 , 34 . The finding of the present study in the OsteoPerio Study suggest that vitamin D may be more influential during the earlier, acute phase of periodontal disease than in prevention of chronic periodontal disease and subsequent tooth loss.…”
Section: Discussionsupporting
confidence: 90%
“…Clinical studies, including RCT, have reported oral supplementation of calcium (1000 mg or more daily) and vitamin D (400 IU) improves periodontal conditions and helps to retain the teeth [18, 7678]. However, a recent longitudinal study indicated that patients with lower (<30 nmol/L) 25-hydroxyvitamin D [25 (OH) D] levels could still be maintained periodontally stable for 5 years [79, 80•]. Therefore, future studies may need to include both the blood test readings, and all the sources for vitamin D for better elucidation of the metabolic dynamics.…”
Section: Interdisciplinary Management Of Osteoporosis and Periodontitismentioning
confidence: 99%
“…Although interest in the association between vitamin D status and the development and progression of periodontal diseases has increased considerably, inconsistent results have appeared so that there are uncertainties as to whether vitamin D insufficiency contributes to the severity of peridontititis . Some investigators have reported that low levels of serum 25(OH)D may be associated with periodontitis independent of bone mineral density (BMD) in the US population, possibly because of BMD‐independent factors, such as the anti‐inflammatory role of vitamin D .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that elevated plasma 25(OH)D is associated with aggressive periodontitis . Some longitudinal studies have demonstrated that patients with lower 25(OH)D levels could still be maintained periodontally stable for 5 years, and those data do not support an association between vitamin D status and tooth loss . Therefore, whether 1,25(OH) 2 D deficiency is causal of susceptibility to periodontitis needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%